2021
DOI: 10.1097/mph.0000000000002095
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Travel Distance to Pediatric Cancer Centers and Rurality on Survival and Treatment Experiences: A Systematic Review

Abstract: Accessing pediatric cancer treatment remains problematic for rural families or those living at increased distances from specialized centers. Rural adult cancer patients or those living far removed from treatment may present with later stage disease, receive different treatments than their closer counterparts, and experience worsened survival. While the financial and psychosocial strain of increased travel is well documented, effects of travel distance on similar outcomes for pediatric cancer patients remain il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…21 This finding is supported by a recent systematic review, which also found an association between rural status and poorer survival in paediatric cancer, while the association between actual travel distance and survival was less consistent. 23 While there initially appeared to be a survival benefit to shorter distance between residence and POU, the supposed benefit remained similar regardless of the distance analysed (20 km, 30 km, 40 km, 50 km, 100 km) and was not significant when analysed without the inclusion of international participants (Table 2). While these international patients did have the greatest distance to travel between place of residence and treating facility, their survival was influenced by additional factors such as having the financial means to seek privately funded medical care in a different country.…”
Section: Discussionmentioning
confidence: 92%
“…21 This finding is supported by a recent systematic review, which also found an association between rural status and poorer survival in paediatric cancer, while the association between actual travel distance and survival was less consistent. 23 While there initially appeared to be a survival benefit to shorter distance between residence and POU, the supposed benefit remained similar regardless of the distance analysed (20 km, 30 km, 40 km, 50 km, 100 km) and was not significant when analysed without the inclusion of international participants (Table 2). While these international patients did have the greatest distance to travel between place of residence and treating facility, their survival was influenced by additional factors such as having the financial means to seek privately funded medical care in a different country.…”
Section: Discussionmentioning
confidence: 92%
“…Examining the effect of travel distance to pediatric cancer centers and rurality on survival and treatment experiences 17 This review focuses on pediatric patients' survival and treatment experiences. The proposed review will focus on adult populations and will not examine survival and treatment experiences.…”
Section: Systematic Review Titlementioning
confidence: 99%
“…A preliminary search of PROSPERO, MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis was conducted and eight similar systematic reviews were identified. Table 1 details each systematic review and how they differ from our proposed review 5,17-23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of such a tool would be to decrease delays in treatment initiation and to make efficient use of available resources. It may also allow for physicians to discuss the option for PT with their patients based on reliable estimates of the potential gain, which will thereby enhance shared decision making on a referral for PT, and whether this might be worthwhile [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%